Wnt signalling in cell division: from mechanisms to tissue engineering - Habib, Shukry James; Acebron, Sergio P. (Trends in cell biology, 2022)
Wnt signalling is an essential player in tissue formation, notably in the regulation of stem cell function. Wnt signalling is best known for its roles in G1/S progression. However, a complex Wnt programme that also mediates mitotic progression and asymmetric cell division (ACD) is emerging. Recent developments in this area have provided mechanistic insights as well as tools to engineer or target Wnt signalling for translational and therapeutic purposes. Here, we discuss the bidirectional relationship between Wnt activity and mitosis. We emphasise how various Wnt-dependent mechanisms control spindle dynamics, chromosome segregation, and ACD. Finally, we illustrate how knowledge about these mechanisms has been successfully employed in tissue engineering for regenerative medicine applications.
Gesehen am 12.01.2023